The Role Of Five Major Shari'ah Legal Maxims (Al-Qawaid Al-Kubra) In The Establishment Of Maqasid Al-shari'ah In Islamic Financial Products: A Discussion On Some Cases - Muhamamd Ridhwan Abdul Aziz; Mohd Shahid Mohd Noh (The International Institute for Science, Technology and Education (IISTE), 2024)
Non-Indexed Publication